(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
This article reviews Spanish-Mexican relations during the second half of the 1920s. In addition to reviewing the details of diplomatic relations, it pays special attention to the links established between Catholic organizations, some intellectuals, the debates raised in Spanish newspapers, as well as some literary references to the events of the Cristero War from 1926 to 1929.